Clinical characteristics, management, and outcomes of pediatric non-infectious uveitis: A multicenter study in Saudi Arabia - Mohammed Nashawi; Suzan A. Alshareef; Salma Alswealh; Nidhal Almohammady; Hamza Fida; Huda Ahmedhussain; Emtenan Basahl; Saddiq Habiballah; Abdulaziz Alshehri; Abdulelah BinYami; Sirin Alfaqih; Mahmoud Majeed; et al. (PLoS ONE, 2026)
Background Pediatric non-infectious uveitis is a challenging condition with significant risks for long-term ocular complications and visual impairment. Limited regional data on its clinical characteristics and outcomes in Saudi Arabia are available. Objective This study aimed to describe the clinical features, management strategies, and outcomes of pediatric non-infectious uveitis in two major medical centers in Saudi Arabia. Methods A retrospective observational study was conducted, including 36 pediatric patients diagnosed with non-infectious uveitis from January 2017 to December 2023. Data were collected on demographic characteristics, clinical presentation, laboratory findings, treatment modalities, and follow-up outcomes at 3, 6, 12, and 24 months. Descriptive and inferential statistics were used for analysis. Results Among the 36 patients, 66.67% were female, and the mean age at diagnosis was 8.99 ± 4.17 years. The most common etiology was juvenile idiopathic arthritis (52.8%), followed by idiopathic uveitis (25%) and Vogt-Koyanagi-Harada disease (19.4%). Bilateral involvement was present in 55.6% of cases, with anterior uveitis being the predominant type (75%). Antinuclear antibody (ANA) positivity was observed in 69.44% of patients. The most frequently used treatments at diagnosis included prednisolone acetate 1% (91.67%) and methotrexate (50%). Over the 2-year follow-up, 86.11% of patients achieved remission, although complications such as synechiae (13.89%), cataracts (8.3%), and band keratopathy (5.56%) were observed. Visual acuity outcomes improved in most cases, although delayed presentation and non-compliance posed challenges. Conclusion Pediatric non-infectious uveitis in Saudi Arabia mirrors global patterns, with JIA being the leading cause. Early diagnosis and biologic therapies have improved remission rates and reduced complications. Future efforts should focus on enhancing screening, patient adherence, and access to advanced therapies to optimize outcomes for affected children.